Los textiles de la tumba del “Señor de Sipán”, Perú - Prümers, Heiko (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
In 1987, excavations at Huaca Rajada directed by Walter Alva brought to light a high-status Moche burial, that became known as the tomb of the “Lord of Sipán”. This paper presents a detailed analysis of all textile remains found in the central coffi n. Of particular interest are various decorated textiles that allow for iconographic comparisons. Data on the layering of the textiles as well as observations regarding the way they had been folded are used to reconstruct the function certain textiles had in the grave context.